2005
DOI: 10.2166/wst.2005.0318
|View full text |Cite
|
Sign up to set email alerts
|

Apatite as an interesting seed to remove phosphorus from wastewater in constructed wetlands

Abstract: Intensive use of phosphates has resulted in high P levels in surface waters and therefore eutrophication problems. Over the last decade many studies have revealed the advantage of using specific materials with efficient phosphorus retention capacities. Recent studies state that Ca materials are of particular interest for long-term retention of P, but can induce negative effects. To improve P retention and avoid negative counter-effects we tested the potential of natural apatites. Apatite sorption was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 12 publications
0
39
0
1
Order By: Relevance
“…The close chemical similarity of HAp to natural bone has led to the extensive research efforts to use synthetic HAp (s-HAp) as a bone substitute and/or replacement in biomedical applications [3]. Besides, HAp and its modified structures have been investigated for drug delivery [4], gene therapy [5],  chromatography [6] and waste water remediation [7]. Over the past, nanostructured materials become very common in biomedical applications [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The close chemical similarity of HAp to natural bone has led to the extensive research efforts to use synthetic HAp (s-HAp) as a bone substitute and/or replacement in biomedical applications [3]. Besides, HAp and its modified structures have been investigated for drug delivery [4], gene therapy [5],  chromatography [6] and waste water remediation [7]. Over the past, nanostructured materials become very common in biomedical applications [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Al respecto, ha sido reportado que en los HC, para obtener una remoción continua de fósforo es muy importante conocer la capacidad de adsorción del ME (Brix et al 2001) y su potencial de saturación (Drizo et al 2002), además de la capacidad de este ME para precipitar el fósforo (Arias y Brix 2005). Por esta razón, recientemente se han estudiado diferentes materiales: grava (Molle et al 2005), apatita (Bellier et al 2006), conchas de ostras (Seo et al 2005) y cenizas y escoria de metal (Xu et al 2006). Por otra parte, Korkuzus et al (2005) reportan que en HC empacados con grava, como es el caso de este estudio, los principales mecanismos de remoción de fósforo son la adsorción y las reacciones de precipitación con Ca, Al, y Fe pero también la asimilación.…”
Section: Efecto Del Caudal De Operación Del Trh Y De La Vfunclassified
“…Also, titanium has been proposed to as a novel, more selective chemo-affinity sorbent candidate. Marie-Luise et al [32] indicated that inorganic phosphate strongly binds and replaces all other ligands on titanium centers. Conversely, despite the silica mesostructure having a huge surface area, its adsorption capacity was small due to the low affinity for phosphorous.…”
Section: Phosphorous Removal Efficiency By the Silica And Titanium Mementioning
confidence: 99%